1999
DOI: 10.1074/jbc.274.38.27287
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Bacteriophage T4-coded Primase (gp61) with the T4 Replication Helicase (gp41) and DNA in Primosome Formation

Abstract: One primase (gp61) and six helicase (gp41) subunits interact to form the bacteriophage T4-coded primosome at the DNA replication fork. In order to map some of the detailed interactions of the primase within the primosome, we have constructed and characterized variants of the gp61 primase that carry kinase tags at either the N or the C terminus of the polypeptide chain. These tagged gp61 constructs have been probed using several analytical methods. Proteolytic digestion and protein kinase protection experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…This is compatible with a ssDNA binding site size for the T4 helicase of approximately 20 nts (18) and is also consistent with the binding site size that has been demonstrated for the closely related hexameric dnaB helicase of E. coli (19). (ii) The primase subunit binds to two ssDNA-bound gp41 subunits at the replication fork (20), bringing it into effective contact with the NTP ligand that lies between these subunits. This primase binding proximity could then specifically "activate" the hydrolysis of the NTP located at this position, while not perturbing the NTP ligands that lie between and stabilize other gp41 subunit interfaces and are not directly adjacent to the primase subunit.…”
Section: Discussionsupporting
confidence: 55%
“…This is compatible with a ssDNA binding site size for the T4 helicase of approximately 20 nts (18) and is also consistent with the binding site size that has been demonstrated for the closely related hexameric dnaB helicase of E. coli (19). (ii) The primase subunit binds to two ssDNA-bound gp41 subunits at the replication fork (20), bringing it into effective contact with the NTP ligand that lies between these subunits. This primase binding proximity could then specifically "activate" the hydrolysis of the NTP located at this position, while not perturbing the NTP ligands that lie between and stabilize other gp41 subunit interfaces and are not directly adjacent to the primase subunit.…”
Section: Discussionsupporting
confidence: 55%
“…Third, translocation of gene 4 protein by the helicase domain transports the primase domain in its search for primase recognition sites. Such a dependency of primase activity on helicase activity also is observed in both the E. coli or T4 phage replication systems in which the two proteins are encoded by separate genes but form a stable complex (6,26,27). Finally, each primase subunit in the hexameric gene 4 protein is in close proximity to neighboring subunits.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, expression of the 56-kDa protein can be an economic strategy for the phage to save production of unnecessary zinc motifs in the 63-kDa subunits in the hexamer. Indeed, it is suggested that less than three molecules of primase form a stable complex with one hexamer of helicase from T4 phage and Bacillus stearothermophilus (6,27).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of the T4 primase to its cognate helicase stimulates helicase activity (47). It has been suggested that three or less primases form a stable complex with a helicase hexamer in T4 phage and Bacillus stearothermophilus (48,49). Bacteriophage T7 expresses equal molar amounts of the 63-and 56-kDa gp4.…”
Section: Discussionmentioning
confidence: 99%